Thin-layer drying characteristics of papaya (Carica papaya) peel using convection oven and microwave drying - Manzoor, Sama; Yusof, Yus Aniza; Chin, Nyuk Ling; Mohamed Amin Tawakkal, Intan Syafinaz; Ahmed, Mohamed Fikry Mohamed; Chang, Lee Sin (Universiti Putra Malaysia Press, 2019)
In this study, papaya (Carica papaya) peel was dried using convection oven and microwave drying methods to investigate the drying kinetics and the drying behavior in the attempt to search for a feasible way to utilize waste peel. Three different drying temperatures (45, 55, and 65 °C) and microwave powers (250, 440, and 600 W) were applied to dry the papaya peel, wherein the drying data were fitted into the following seven drying kinetic models: Lewis, Page, Modified Page, Henderson and Pabis, Logarithmic, Two-Term, and Approximation of Diffusion models. The study outcomes indicated that the Page model emerged as the best fitted model for oven drying of papaya peels with the highest coefficient of determination (R2) value (0.994-0.996) for all the three temperatures. As for microwave drying, the Approximation of Diffusion model exhibited the best fit owing to the highest R2 value (0.996-0.999) for all the three powers. The effective moisture diffusivity values for convection oven and microwave drying methods ranged from 6.65 x 10-08 to 4.35 x 10-07 and from 2.43 x 10-07 to 6.67 x 10-07, respectively. Additionally, the activation energy values were recorded at 61.301 kJ/mol and 46.621 W/g for oven and microwave drying methods, respectively.